The worst day of my life ever! - Cook, Julia 1964-; De Weerd, Kelsey (Nebraska Boys Town Press, 2011)
When RJ learns to use such skills as listening and following instructions, he has the best day of his life.
K-6.
Keywords: Success -- Fiction; Listening -- Fiction; Attention -- Fiction; Thought and thinking -- Fiction